Co-branding - An Innovative Strategy in Management - Akula, Ravi (Indian Journal of Marketing, 2008)
Liberalization in India has brought changes in technology, quality, service work culture and undoubtedly fierce competition. As Kotler, Philip says, "Companies should think about the millennium as a golden opportunity to gain mind share and heart share". It should be noted that these mind shares highlighted by Kotler are nothing but carving out brands in the customers mind. Marketers to capture share of mind and share of heart adopt innovative tools and techniques. Brands with varying dimensions of attributes, benefits, values, culture, personality and users have the real power to generate wealth. Brands, which are storing in these dimensions command respectable position in terms of sales, reputation, image etc, in the market.